Archival research on integrated reporting: a systematic review of main drivers and the impact of integrated reporting on firm value - Patrick Velte (Journal of Management and Governance, 2021)
Integrated reporting (IR) represents an innovative approach to business reporting especially by Public Interest Entities (PIEs). In addition to financial capital, the integrated report includes material information about manufactured, intellectual, human, social and relational, and natural capitals. Although there has been a steady growth in empirical IR research, there is—as yet—no literature review on the business case for IR. Thus, the purpose of this study is to convey a detailed understanding of the governance-, (non) financial performance-, and reporting-related determinants of IR and its contribution to firm value in line with the business case argument. To do so, we selected 85 quantitative peer-reviewed archival studies on that topic. We have then differentiated said studies between those that focus on IR adoption versus those that focus on IR quality, with a legitimacy- and stakeholder-theory-based framework. This differentiation is crucial, to stress the challenges of greenwashing policies and information overload. Here, in contrast to former literature reviews on IR, we provide new insights into this emerging research topic and concentrate on archival IR research. We are also interested in recent moderator- and mediator analysis in archival IR research since the business case argument for IR may require a specific environment, in addition to the main variables we have included. We likewise give a detailed overview of included variables and proxies and compare their main statistical effects. Our literature review demonstrates that (1) board composition and (2) stakeholder pressure positively influence IR quality; whereas (3) (non) financial performance leads to increased IR adoption and quality. We also find that both IR adoption and IR quality are linked with positive consequences on firm valuation, as they lead to higher total performance measures. Last but not least, this analysis includes useful recommendations for future IR research.
Keywords: M41; M48; Q56; 650; Integrated reporting; Corporate governance; Financial performance; Legitimacy theory; Stakeholder theory; Archival research